2020
DOI: 10.1177/0963689719885077
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells-mediated Transcriptomic Regulation of Leukemic Cells in Delivering Anti-tumorigenic Effects

Abstract: Treatment of leukemia has become much difficult because of resistance to the existing anticancer therapies. This has thus expedited the search for alternativ therapies, and one of these is the exploitation of mesenchymal stem cells (MSCs) towards control of tumor cells. The present study investigated the effect of human umbilical cord-derived MSCs (UC-MSCs) on the proliferation of leukemic cells and gauged the transcriptomic modulation and the signaling pathways potentially affected by UC-MSCs. The inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Notably, treating HCC with MSCs alone or in combination with 5FU predominantly arrest the cell cycle progression of tumor cells in the G0/G1 phase of the cell cycle, and thus fewer cells proceeded to the subsequent S and G2/M phases. The observed disruption of cell cycle progression in the tumor cells suggests that treatment with MSCs leads to potent growth inhibition of tumor cells without being subject to apoptosis (Sarmadi, Ahmadloo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, treating HCC with MSCs alone or in combination with 5FU predominantly arrest the cell cycle progression of tumor cells in the G0/G1 phase of the cell cycle, and thus fewer cells proceeded to the subsequent S and G2/M phases. The observed disruption of cell cycle progression in the tumor cells suggests that treatment with MSCs leads to potent growth inhibition of tumor cells without being subject to apoptosis (Sarmadi, Ahmadloo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The role of MSCs in tumorigenesis is subject to discussion, as several studies have demonstrated that MSCs have a protective or tumor-suppressive role [38][39][40][41]. Others have demonstrated that MSCs may aid, promote and direct tumor formation in a wide range of primary tumors [42][43][44][45][46].…”
Section: Plos Onementioning
confidence: 99%
“…Sarmadi et al showed that human umbilical cord MSCs affected the proliferation of leukemic cells—the growth of tumor cells was stopped at the G0/G1 phase. This result may be associated with the impaired expression of genes encoding cell cycle regulators, such as cell division protein kinase 6 (CDK6), cyclin E2 (CCNE2), cyclin-dependent kinase inhibitor (CDKN) 1A, CDKN2A, dumbbell former 4 protein (DBF4), mouse double minute 2 homolog (MDM2), proteasome activator complex subunit 3 (PSME3), and G0/G1 switch 2 (G0S2) [ 81 ].…”
Section: Antitumor Properties Of Mesenchymal Stromal Cellsmentioning
confidence: 99%